Small and Intermediate Calcium Activated Potassium Channels in the Heart: Role and Strategies in the Treatment of Cardiovascular Diseases - Weisbrod, David (Frontiers in Physiology, 2020)
Calcium-activated potassium channels are a heterogeneous family of channels that, despite their different biophysical characteristics, structures, and pharmacological signatures, play a role of transducer between the ubiquitous intracellular calcium signaling and the electric variations of the membrane. Although this family of channels was extensively described in various excitable and non-excitable tissues, an increasing amount of evidences shows their functional role in the heart. This review aims to focus on the physiological role and the contribution of the small and intermediate calcium-activated potassium channels in cardiac pathologies.